DIRECTIONS FOR THE DEVELOPMENT OF SMALL BUSINESS AND ENTREPRENEURSHIP IN UZBEKISTAN - Ismoilov Ravshanjon Bakhritdinovich; Muminov Sodiqjon Tukhtasinovich (Galaxy International Interdisciplinary Research Journal, 2021)
This article describes the development of small business and entrepreneurship in Uzbekistan.